KEBIJAKAN PENYELENGGARAAN PERPARKIRAN DI KOTA PEKANBARU TAHUN 2021-2023 - Fadilah, Muhammad Arief; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the policy and obstacles faced by the Pekanbaru City Government in implementing the parking retribution policy and to provide recommendations to enhance its effectiveness. The research employs a qualitative approach with in-depth interviews conducted with relevant officials, particularly those in the Parking Management Unit (UPT Perpakiran) of Pekanbaru City. The study is based on George Edward III’s implementation theory, which consists of four key indicators: communication, resources, disposition (attitude), and bureaucratic structure. The findings reveal several major challenges in implementing the parking retribution policy, including insufficient dissemination of information to parking attendants, inadequate supervision, and low public awareness regarding the importance of parking regulations. Additionally, the management of facilities and human resources remains a challenge in ensuring optimal parking services. To address these issues, this study recommends several measures, such as increasing public outreach and training programs for parking attendants, leveraging technology for more efficient supervision, and conducting educational campaigns to raise public awareness of the benefits of parking retribution for urban development. Enhancing communication between parking coordinators and attendants is also crucial to minimizing miscommunication and improving compliance. It is expected that the findings of this study can serve as valuable input for the Pekanbaru City Government in formulating more effective policies for parking management and local revenue enhancement. Keywords: Parking Policy, Communication, Source, Disposition, Birocration.